Standoff Raman Spectroscopy of C4 Explosive and Study the Effect of Integration Time and Laser Power - Mohammad, Mohammad R; Abdulzahraa, Haider G; Hadi, Naseer M (Al-Nahrain Journal of Science, 2017)
In this paper standoff Raman spectroscopy SRS system for explosive materials is developed. Standoff Raman detection of C4 substance under dark laboratory condition at 4 m distance is achieved. A frequency doubled Nd:YAG laser at 532 nm excitation is used. The Raman scattered light is collected by a telescope and then transferred via fiber optics cable to spectrograph and finally into CCD detector. Notch filter used to reject Rayleigh scattering light. Carbon tetrachloride CCL4 and Acetone (CH3)2CO are used as a calibration standard for the Raman measurements because of their strong and intensive scattering capability. Raman measurement of C4 explosive is also acquired using conventional Raman microscopy for verification of standoff Raman measurements. The effects of integration time and laser power on Raman cross section under dark condition were studied. Standoff Raman detection of C4 substance at 4 m distance under partially illuminated condition has been achieved and hence the effect of higher integration time was studied under the same condition.